Decadal co-variability of Atlantic SSTs and western Amazon dry-season hydroclimate in observations and CMIP5 simulations - Fernandes, K.; Giannini, A.; Verchot, Louis V.; Baethgen, Walter E.; Pinedo Vasquez, M. (Wiley, 2015)
The unusual severity and return time of the 2005 and 2010 dry‐season droughts in western Amazon is attributed partly to decadal climate fluctuations and a modest drying trend. Decadal variability of western Amazon hydroclimate is highly correlated to the Atlantic sea surface temperature (SST) north‐south gradient (NSG). Shifts of dry and wet events frequencies are also related to the NSG phase, with a 66% chance of 3+ years of dry events per decade when NSG > 0 and 19% when NSG < 0. The western Amazon and NSG decadal covariability is well reproduced in general circulation models (GCMs) historical (HIST) and preindustrial control (PIC) experiments of the Coupled Model Intercomparison Project Phase 5 (CMIP5). The HIST and PIC also reproduce the shifts in dry and wet events probabilities, indicating potential for decadal predictability based on GCMs. Persistence of the current NSG positive phase favors above normal frequency of western Amazon dry events in coming decades.